Europeus e indígenas : relações interculturais no Guairá nos séculos XVI e XVII - Chagas, Nádia Moreira (2010)
This dissertation approaches the History ofthe Guairá, a territory under the Spanish authority in the southern America, throughout the XVI century to the first decades of the XVII century. it addresses the physical and population aspects of the area before and after the Europeans arrival. It demonstrates the European presence in the area, during the first centuries of the colonization giving emphasis to the intercultural relations which were established there, approaching how the European presence encouraged changes in the way of living of the indian population and in the territory itseif. it highlights the unnumbered Indian presence, mainly the Guarani (widespread group in the Guaira territory), the European interest in exploiting the labor of these populations and how the Indians reacted to that It emphasizes the how the Jesuítas arrived and organized the missionary work among the Indians, how they fostered the gospel and secular teaching among them and the resistance they intended to stand up to the paulistas pioneers. It presents also the journey of the paulistas pioneers to the Guairá's inland searching for Indians to siave and ensure the forced labor in Sao Paulo, and the violent conflicts that were resulted because of these encountering. I concluded, emphasizing that the intercultural relations established in Guairá during the defined years, happened in opposition to the Indian interest, benefiting the Europeans, even though it had been understood that the first inhabitants ofthe coiony were not passive individuals before the land conquest.